Surveillance virů prenosných komáry na Breclavsku v povodnovém roce 1997 - Hubálek, Z; Halouzka, J; Juricová, Z; Príkazský, Z; Záková, J; Sebesta, O (Epidemiologie, mikrobiologie, imunologie, 1999)
In July 1997, devastating floods occurred after heavy rains in Moravia, Czech Republic. Mosquito populations increased abruptly in the flooded area thereafter. We carried out a surveillance for mosquito-borne virus infections in the Breclav area, South Moravia, including serosurveys of inhabitants. A total of 11,334 female mosquitoes in 117 pools (9,100 Aedes vexans, 917 A. cinereus, 11 A. cantans, 1,074 A. sticticus and 232 Culex pipiens pipiens) were examined by virological methods. Seven virus isolates were obtained: six of them Tahyna virus (Aedes vexans 5, A. cinereus 1), while one was West Nile (WN) virus (Culex p. pipiens--first isolation in the Czech Republic). Sera of 619 local inhabitants were examined in plaque-reduction neutralization test, and antibodies to Tahyna virus were detected in 333 (53.8%) and to WN virus in 13 (2.1%). In 72 individuals, paired sera were sampled: a significant increase of antibody titre was detected once against Tahyna virus (a subclinical infection) and 4 times against WN virus (two children had an illness compatible with WN fever). Of the nine remaining WN seroreactors, three other revealed clinical symptoms compatible with WN fever in summer 1997. The data indicate WN virus activity in the Breclav area, and describe the first cases of WN fever in Central Europe. The WN virus should not be underestimated as a potential agent of local epidemics even in the temperate climate of Central Europe. Environmental factors including human activities which enhance vector population densities (heavy rains followed by floods, irrigation, higher temperature) can produce an increased incidence of mosquito-borne diseases, including WN fever.
Keywords: viry kalifornské encefalitidy; západonilská horečka; Male; protilátky virové; Seroepidemiologic Studies; West Nile Fever; West Nile virus; séroepidemiologické studie; Viruses; kalifornská encefalitida; Adolescent; Česká republika; Child; viry; Encephalitis, California; dítě; Adult; Aged; dospělí; mužské pohlaví; senioři; hmyz - vektory; mladiství; Czech Republic; senioři nad 80 let; Animals; lidé; ženské pohlaví; Encephalitis Virus, California; Humans; zvířata; Culicidae; virus západního Nilu; Aged, 80 and over; Insect Vectors; Antibodies, Viral; Disasters; katastrofy; Female; lidé středního věku; Middle Aged